2018
DOI: 10.1051/matecconf/201816506010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the surface morphology on the cyclic deformation behavior of HSD® 600 steel

Abstract: Abstract. The presented research work investigates the fatigue properties in the low cycle fatigue (LCF) regime of the high manganese metastable austenitic High Strength and Ductility (HSD ® ) 600 TWIP steel dependent on its surface morphology. The steel features, according to its chemical composition following the alloying concept Mn-Al-Si-C and heat treatment, a fully austenitic microstructure that shows deformation induced twinning at ambient temperature. Due to this microstructural deformation mechanism, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Flat specimens with longitudinal axis transverse to rolling direction were taken by water-jet cutting. Note that the monotonic properties given in Reference [53] do not differ between longitudinal and transverse direction. To achieve different surface morphologies, the gage length surfaces were milled with the vectors of feed and cutting speed against each other (up milling) and with both vectors in the same direction (down milling), respectively.…”
Section: Specimen Manufacturing With Different Surface Morphologiesmentioning
confidence: 86%
See 3 more Smart Citations
“…Flat specimens with longitudinal axis transverse to rolling direction were taken by water-jet cutting. Note that the monotonic properties given in Reference [53] do not differ between longitudinal and transverse direction. To achieve different surface morphologies, the gage length surfaces were milled with the vectors of feed and cutting speed against each other (up milling) and with both vectors in the same direction (down milling), respectively.…”
Section: Specimen Manufacturing With Different Surface Morphologiesmentioning
confidence: 86%
“…Additionally, the magnetic properties were measured in situ with a Feritscope ® "MP30E" Helmut Fischer (Helmut Fischer GmbH, Sindelfingen, Germany) for specimens with the as-received morphology, i.e., with a so-called rolling skin, because this rolling skin showed phase transformation from γ-austenite to α'-martensite during fatigue tests while the austenitic microstructure of the bulk material was stable against phase transformation. The rolling skin was removed in case of the other investigated morphologies, see Reference [53] for further details.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The accumulation of plastic deformation resulting from the action of cyclic mechanical stress can lead to the initiation and propagation of fatigue cracks in the regions of stress concentration. In [ 25 , 26 , 27 , 28 , 29 , 30 ], the fatigue behavior of the Fe-Mn-Si engineering alloys was studied at relatively small deformations; it is shown that the mechanocycling process is accompanied by an initial hardening followed by softening and secondary cyclic hardening.…”
Section: Introductionmentioning
confidence: 99%